Cost of care of chronic non-communicable diseases in Jamaican patients: the role of obesity - Fray-Aiken, Christine M.; Wilks, Rainford J.; Abdulkadri, Abdullahi O.; McCaw-Binns, Affette M. (Farmeconomia. Health Economics and Therapeutic Pathways, 2016)
OBJECTIVE: To estimate the economic cost of Chronic Non-Communicable Diseases (CNCDs) and the portion attributable to obesity among patients in Jamaica.METHODS: The cost-of-illness approach was used to estimate the cost of care in a hospital setting in Jamaica for type 2 diabetes mellitus, hypertension, coronary heart disease, stroke, gallbladder disease, breast cancer, colon cancer, osteoarthritis, and high cholesterol. Cost and service utilization data were collected from the hospital records of all patients with these diseases who visited the University Hospital of the West Indies (UHWI) during 2006. Patients were included in the study if they were between15 and 74 years of age and if female, were not pregnant during that year. Costs were categorized as direct or indirect. Direct costs included costs for prescription drugs, consultation visits (emergency and clinic visits), hospitalizations, allied health services, diagnostic and treatment procedures. Indirect costs included costs attributed to premature mortality, disability (permanent and temporary), and absenteeism. Indirect costs were discounted at 3% rate.RESULTS: The sample consisted of 554 patients (40%) males (60%) females. The economic burden of the nine diseases was estimated at US$ 5,672,618 (males 37%; females 63%) and the portion attributable to obesity amounted to US$ 1,157,173 (males 23%; females 77%). Total direct cost was estimated at US$ 3,740,377 with female patients accounting for 69.9% of this cost. Total indirect cost was estimated at US$ 1,932,241 with female patients accounting for 50.6% of this cost. The greater cost among women was not found to be statistically significant. Overall, on a per capita basis, males and females accrued similar costs-of-illness (US$ 9,451.75 vs. US$ 10,758.18).CONCLUSIONS: In a country with per capita GDP of less than US$ 5,300, a per capita annual cost of illness of US$ 10,239 for CNCDs is excessive and has detrimental implications for the health and development of Jamaica.